PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA SEKTOR PROPERTI, REAL ESTATE, DAN KONSTRUKSI - Eklesia Hosana Randi Pratiwi (Business Accounting Review, 2016)
Today's world is so interested in the application of the concept of Corporate Social Responsibility (CSR) in the business world, because they are considered by implementing CSR, the company is able to survive and achieve its objectives by in an attention to the stakeholder. The aim of this study was to examine the affect of CSR on the firm value in the property, real estate, and building construction sector that listed on the Indonesia Stock Exchange in 2009 until 2013. The CSR was measured based on the criteria of the Global Reporting Index (GRI) and firm value which is proxied by Tobin's Q. In this study, there were several control variables: Firm Size (Fsize), Debt to Equity Ratio (DER), and Market Share (MShare). The data processing of 108 firm years using linear regression with SPSS version 20. Results from this study indicated positive response of CSR to Tobin's Q. The control variables Fsize and DER had no effect on Tobin's Q, while Mshare had positive influence on Tobin's Q.